Associations of variants in FTO and near MC4R with obesity traits in South Asian Indians. - Vasan, S; Fall, T; Neville, M; Antonisamy, B; Fall, C; Geethanjali, F; Gu, H; Raghupathy, P; Samuel, P; Thomas, N; Brismar, K; Ingelsson, E; et al. (2012)
Recent genome-wide association studies show that loci in FTO and melanocortin 4 receptor (MC4R) associate with obesity-related traits. Outside Western populations the associations between these variants have not always been consistent and in Indians it has been suggested that FTO relates to diabetes without an obvious intermediary obesity phenotype. We investigated the association between genetic variants in FTO (rs9939609) and near MC4R (rs17782313) with obesity- and type 2 diabetes (T2DM)-related traits in a longitudinal birth cohort of 2,151 healthy individuals from the Vellore birth cohort in South India. The FTO locus displayed significant associations with several conventional obesity-related anthropometric traits. The per allele increase is about 1% for BMI, waist circumference (WC), hip circumference (HC), and waist-hip ratio. Consistent associations were observed for adipose tissue-specific measurements such as skinfold thickness reinforcing the association with obesity-related traits. Obesity associations for the MC4R locus were weak or nonsignificant but a signal for height (P < 0.001) was observed. The effect on obesity-related traits for FTO was seen in adulthood, but not at younger ages. The loci also showed nominal associations with increased blood glucose but these associations were lost on BMI adjustment. The effect of FTO on obesity-related traits was driven by an urban environmental influence. We conclude that rs9939609 variant in the FTO locus is associated with measures of adiposity and metabolic consequences in South Indians with an enhanced effect associated with urban living. The detection of these associations in Indians is challenging because conventional anthropometric obesity measures work poorly in the Indian "thin-fat" phenotype.